Role of Knowledge Networks in Distance Learning - Muhammad Zaheer (PJDOL, 2023)
This study is aimed at exploring the knowledge sharing methods adopted by the students in distance learning mode. Students studying in distance learning do not have formal/regular classes where they can go and have academic discussions. Though, this convenience of not attending the classes facilitates many but at the same time poses certain challenges as burden of knowledge acquisition shifts towards the student alone. This was a qualitative study using grounded theory methodology to know how students in distance learning share their academic problems and seek solution. A sample of twenty students was selected, through purposive sampling, from three universities of Pakistan. For data collection, semistructured interviews were conducted. It was found that students create online groups/communities to help each other and overcome the absence of face to face interactions.